2014
DOI: 10.3349/ymj.2014.55.4.1115
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Gastrocnemius Muscle Volume Using Ultrasonography in Children with Spastic Cerebral Palsy

Abstract: PurposeThis study aimed to investigate useful parameters for estimating gastrocnemius (GCM) muscle volume (MV) using ultrasonography (US) and anthropometry in children with spastic cerebral palsy (CP).Materials and MethodsEighteen legs from nine children with spastic CP aged 2 to 6 years were investigated in this study. Tibial length (TL) of each leg was measured and muscle thickness (MT) and anatomical cross-sectional area (aCSA) of GCM muscles were assessed using US. The volume of the GCM was measured by mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(75 citation statements)
references
References 44 publications
4
71
0
Order By: Relevance
“…However, our typically developing children were both taller (105cm for a 48‐month‐old child vs 102cm in the study of Barber et al) and heavier (18kg vs 16kg). Furthermore, our measurements of PCSA were similar to previous findings …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our typically developing children were both taller (105cm for a 48‐month‐old child vs 102cm in the study of Barber et al) and heavier (18kg vs 16kg). Furthermore, our measurements of PCSA were similar to previous findings …”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our measurements of PCSA were similar to previous findings. 13,20,21 The previous studies 12,13 found no differences in height, weight, or fibula length between typically developing children and those with CP, and the difference in muscle volume could therefore be ascribed to lack of muscle growth. Similarly, we only found a small difference in the overall growth of the children with CP compared with the significantly reduced rate of medial gastrocnemius muscle volume increment ( Figs.…”
Section: Discussionmentioning
confidence: 92%
“…Musculoskeletal ultrasonography is a valid clinical tool for diagnosing neuromuscular disease in children, but less is known about the utility of muscle quality and quantity for assessing physical performance in healthy children. The results of this investigation can be summarized by 4 points: (1) almost all of the bivariate correlations were statistically significant, and several significant correlations existed after controlling for age and mass; (2) RF muscle thickness showed the strongest correlations with the dependent variables; (3) RTD, but not peak torque, correlated with muscle thickness, but not echo intensity; (4) of the 7 athletic performance and isometric strength attributes, the dependent variable with the strongest correlations was agility.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported normative values, compared data obtained from ultrasonography to that from MRI, examined test–retest reliability, and assessed growth and development . However, the overwhelming majority of ultrasonography studies in children have assessed its ability to diagnose neuromuscular diseases . Pillen et al first reported that echo intensity could correctly differentiate healthy versus diseased muscle with 92% accuracy.…”
mentioning
confidence: 99%
“…Cross‐sectional area was measured at the approximate rupture site on injured limbs and at a point on the free tendon immediately distal to the soleus myotendinous junction in healthy limbs . Medial and lateral gastrocnemius cross sectional area was measured using extended field of view settings at 25% tibial length distal to the medial tibial plateau . Soleus thickness was assessed by measuring between superficial and deep fascial lines imaged in long axis at an area 30% of tibial length proximal to the medial malleolus .…”
Section: Methodsmentioning
confidence: 99%